STUDI AWAL DATA LOGGER SENSOR ALIRAN FLUIDA BERBASIS MIKROKONTROLER ATMEGA 328 (ARDUINO UNO) - Ulfah Zuhaeriah; Iwan Sugihartono; Bernadus Herdi Sirenden (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2016)
Data logger is a system that can record and save the data continously. A data logger needs controlling system to operate it. One of controlling systems that can be used is Atmega 328 microcontroller (arduino uno). The aim of this research is to build a data logger system based arduino uno which be able reading pulse width data. The pulse width data is output data from RF pickoff sensor. The function of this sensor is to catch magnetic signal from flowmeter turbin. The data logger system is built by Python language to process data on Personal Computer (PC). On this data logger system, arduino will do serial communication using python. The result indicates the pulse width value is below 500 Î¼s. Keywords: Data Logger, Atmega 328 microcontroller, RF Pickoff Sensor, Pulse Width.